Resurgence of BK virus following Covid‐19 in kidney transplant recipients. Issue 1 (23rd September 2020) - Masset, Christophe; Ville, Simon; Halary, Franck; Gaborit, Benjamin; Bressolette‐Bodin, Celine; Deltombe, Clément; Dujardin, Amaury; Jacquemont, Lola; Lebot, Sabine; Kervella, Delphine; Figueres, Lucille; Cantarovich, Diego; et al.
Abstract: Kidney transplant recipients have been supposed vulnerable to severe Covid‐19 infection, due to their comorbidities and immunosuppressive therapies. Mild‐term complications of Covid‐19 are currently unknown, especially in this population. Herein, we report two cases of BKV replication after non‐severe SARS‐CoV‐2 infection. The first case was a 59‐year‐old man, transplanted 3 months ago, with recent history of slight BKV viremia (3.3 log10 DNA copies/ml). Despite strong reduction of maintenance immunosuppression (interruption of mycophenolic acid and important decrease of calcineurin inhibitors), BKV replication largely increased after Covid‐19 and viremia persisted at 4.5 log copy/ml few months later. The second case was a 53‐year‐old woman, transplanted 15 years ago. She had a recent history of BKV cystitis, which resolved with a decrease of MPA dosage. Few weeks after SARS‐CoV‐2 infection, she presented recurrence of lower urinary tract symptoms. Our reports highlight that SARS‐CoV‐2 infection, even without severity, could disrupt immune system and particularly lymphocytes, thus leading to viral replication. Monitoring of viral replications after Covid‐19 in kidney transplant recipients could permit to confirm these preliminary observations.